2019
DOI: 10.3390/met9020241
|View full text |Cite
|
Sign up to set email alerts
|

Sn-0.5Cu(-x)Al Solder Alloys: Microstructure-Related Aspects and Tensile Properties Responses

Abstract: In this study, experiments were conducted to analyze the effect of 0.05 and 0.1 wt.% Al additions during the unsteady-state growth of the Sn-0.5wt.%Cu solder alloy. Various as-solidified specimens of each alloy were selected so that tensile tests could also be performed. Microstructural aspects such as the dimensions of primary, λ1, and secondary, λ2, dendritic arrays, and intermetallic compounds (IMCs) morphologies were comparatively assessed for the three tested compositions, that is, Sn-0.5wt.%Cu, Sn-0.5wt.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…It is observed that despite the two morphological transitions in the Bi‐rich matrix, the power‐type experimental laws given by λ 1 = 331.8 (Tfalse˙) −0.55 and λ 2 = 16.8 ( V ) −1.1 may represent the evolution of these microstructural spacings for all the studied Bi–Sb alloys. The use of the −0.55 exponent in the experimental law has been demonstrated to effectively describe the Tfalse˙ dependence on the growth of λ 1 for several metallic alloys . Despite many studies having found equations given by λ 2 = constant ( V ) −2/3 for different alloy systems, the effects of lateral solute segregation on the wavelengths of instabilities along the sides of primary dendritic stems for Bi‐based alloys are still not well understood.…”
Section: Resultsmentioning
confidence: 99%
“…It is observed that despite the two morphological transitions in the Bi‐rich matrix, the power‐type experimental laws given by λ 1 = 331.8 (Tfalse˙) −0.55 and λ 2 = 16.8 ( V ) −1.1 may represent the evolution of these microstructural spacings for all the studied Bi–Sb alloys. The use of the −0.55 exponent in the experimental law has been demonstrated to effectively describe the Tfalse˙ dependence on the growth of λ 1 for several metallic alloys . Despite many studies having found equations given by λ 2 = constant ( V ) −2/3 for different alloy systems, the effects of lateral solute segregation on the wavelengths of instabilities along the sides of primary dendritic stems for Bi‐based alloys are still not well understood.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] employed directional solidification systems to allow microstructural and tensile data to be assessed. After solidifying the casting, transverse (perpendicular to the solidification direction) and longitudinal samples (at various sections from the cooled bottom of the castings) were removed of alloy casting for the metallographic procedure using optical microscopy.…”
Section: Database Generationmentioning
confidence: 99%
“…The secondary (λ2) and tertiary (λ3) dendritic arm spacings were measured by using the linear intercept method using longitudinal sections (parallel to the extraction direction of heat) and transversal, respectively. The same linear intercept method was adopted in some of the studies [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] for determining λfino, λcoarse, λcu6Sn5, λAg3Sn and λZn. Moreover, the tensile properties of the alloys were determined through tensile tests at different positions in the castings with strain rates in the order of 10 -3 s -1 .…”
Section: Database Generationmentioning
confidence: 99%